2023
DOI: 10.1002/adfm.202215041
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Perovskite Lattice and Suppression of Sn2+/Sn4+ Oxidation via Formamidine Acetate for High Efficiency Tin Perovskite Solar Cells

Abstract: Tin halide lead‐free perovskite solar cells (TPSCs) have received tremendous research interest recently due to their nearly ideal bandgap, broad light absorption, non‐toxicity, and environmental friendliness. However, the uncontrollable crystallization process and the facile oxidation of Sn2+ limit the further increase of power conversion efficiency (PCE). To solve these problems, a series of acetates are introduced into the perovskite precursor solution to regulate the crystallization process. It is revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 55 publications
0
44
0
Order By: Relevance
“…[ 68,69 ] More importantly, the DOS of the TPSCs treated with the antioxidant strategy was degraded, which meaning the defect states in the tin perovskite crystals gradually increase as the oxidation occurs, leading to the creation of various degrees of nonradiative recombination centers between energy levels. [ 69,70 ] As shown in Figure 4e, according to Equation (17) [ 68,71 ] normalΔVOCbadbreak=0.33emL0.33emq2DOSnormalΔQ0.33em$$\begin{eqnarray} \def\eqcellsep{&}\begin{array}{*{20}{c}} {\Delta {V}_{{\rm{OC}}} = \ \frac{{L\ {q}^2}}{{{\rm{DOS}}*\Delta Q}}\ } \end{array} \end{eqnarray}$$where L is the thickness of perovskite film, Δ Q is the short‐circuit photogenerated charge, ∆ V oc is the V oc rise generated under gradient intensity of transient light irradiation. [ 71,72 ] With the density of states gradually increases, ∆ V oc will reduce, implying that more photogenerated carriers will undergo nonradiative recombination between the valence and the conduction bands, which indirectly explains the V loss in TPSCs.…”
Section: The Effects Of Sn(ii) Oxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 68,69 ] More importantly, the DOS of the TPSCs treated with the antioxidant strategy was degraded, which meaning the defect states in the tin perovskite crystals gradually increase as the oxidation occurs, leading to the creation of various degrees of nonradiative recombination centers between energy levels. [ 69,70 ] As shown in Figure 4e, according to Equation (17) [ 68,71 ] normalΔVOCbadbreak=0.33emL0.33emq2DOSnormalΔQ0.33em$$\begin{eqnarray} \def\eqcellsep{&}\begin{array}{*{20}{c}} {\Delta {V}_{{\rm{OC}}} = \ \frac{{L\ {q}^2}}{{{\rm{DOS}}*\Delta Q}}\ } \end{array} \end{eqnarray}$$where L is the thickness of perovskite film, Δ Q is the short‐circuit photogenerated charge, ∆ V oc is the V oc rise generated under gradient intensity of transient light irradiation. [ 71,72 ] With the density of states gradually increases, ∆ V oc will reduce, implying that more photogenerated carriers will undergo nonradiative recombination between the valence and the conduction bands, which indirectly explains the V loss in TPSCs.…”
Section: The Effects Of Sn(ii) Oxidationmentioning
confidence: 99%
“…It was demonstrated that the CO bond in FAAc not only stabilized the lattice more effectively, but also had the effect of inhibiting Sn(II) oxidation. [ 70 ] Kim et al. reported that formamidinium thiocyanate (FASCN) had a strong interaction with Sn 2+ , which greatly prevents the oxidation of quasi‐2D tin perovskite during film formation.…”
Section: Strategies For Suppressing Sn(ii)/sn(iv) Oxidation In Tpscsmentioning
confidence: 99%
See 1 more Smart Citation
“…8−10 Furthermore, the rapid crystallization process of TPSCs is identified as a key factor affecting crystallinity and orientation, structural and phase distribution, film morphology, and Sn-related defects in tin perovskite films. 11−14 Many strategies have been implemented to address these issues for TPSCs, which include the attempt of reducing additives (e.g., metallic Sn powder, 15 hydrazine vapor, 16 pyrazine, 17 and SnF 2 12 ), dimensional regulation with more stable 2D phase, 11,18,19 and solvent engineering. 20 Therein, dimensional-mixed tin halide perovskites show an alleviative ptype self-doping effect owing to the quantum confinement effect.…”
mentioning
confidence: 99%
“…Many strategies have been implemented to address these issues for TPSCs, which include the attempt of reducing additives (e.g., metallic Sn powder, hydrazine vapor, pyrazine, and SnF 2 ), dimensional regulation with more stable 2D phase, ,, and solvent engineering . Therein, dimensional-mixed tin halide perovskites show an alleviative p-type self-doping effect owing to the quantum confinement effect. , Introducing bulky organic spacers such as phenylethylammonium (PEA + ), butylammonium (BA + ), ethylammonium (EA + ), and 5-ammoniumvaleric acid (5-AVA + ) in tin perovskites gives a reduced dimensionality with a slower crystallization and retarded crystal growth rate. The quasi-2D tin perovskites usually have a range of phases with different layer numbers ( n ) from 1 to ∞. , These perovskites could enhance the water and oxygen resistance, thus leading to robust device stability.…”
mentioning
confidence: 99%